Impact of the Relative Submergence on Turbulence Structures in Open‐Channel Flow Through Arrays of Large Spherical Roughness Elements - Zhengdao Tang; Thorsten Stoesser; Lei Huang; Yan Liu; Hongwei Fang (Water Resources Research, 2025)
Abstract This study investigates the impact of relative submergence, defined as the ratio of water depth to the diameter of boulders (k = H/D), on turbulence structures in flow through boulder arrays. The large‐eddy simulation method is employed to simulate flow through boulder arrays across a range of k values from 0.25 to 3.50. Within this range, three distinct flow regimes are identified: low (k = 0.25), intermediate (k = 0.75 and 1.25), and high (k = 2.0 and 3.5) relative submergence regimes. Across these three regimes, distributions of time‐averaged velocities, secondary flow, turbulent kinetic energy, and dominant turbulence structures in the wakes of boulders exhibit significant variations. The wake of boulders, characterized by recirculation flow, only manifests at k ≥ 0.75 and is more pronounced at higher k values. Particularly at k = 3.5, funnel vortices in the wake and secondary flow at the sides of boulders develop, enhancing vertical momentum exchange. Three types of coherent structures are identified within the wake: (a) the near‐bed hairpin vortex with a wavelength (λ) of 0.8D at the lowest k, (b) the lateral flapping of boulder wakes with λ=2.1D intermediate k, and (c) the meandering of high‐speed streaks at the side of boulders with λ=10D at high k. These structures alter the distribution of the near‐bed Reynolds shear stresses (RSS) and contribute up to 20% of the near‐bed RSS. At k ≤ 1.25, a region of low near‐bed shear stress appears upstream of boulders, while it shifts to the wake of boulders at k = 3.5, contributing the observed variations in deposition patterns at different k values as reported by Papanicolaou et al. (2018, https://doi.org/10.1029/2018jf004753). In addition, the two bedload periodicities reported in the experiment of Papanicolaou et al. (2018, https://doi.org/10.1029/2018jf004753) are justified by the ratio of the wavelength of lateral flapping of boulder wakes to that of meandering of low‐ and high‐speed streaks.